Elaphuri Davidiani Cornu Improves Depressive-Like Behavior in Mice and Increases Neurotrophic Factor Expression in Mouse Primary Astrocytes via cAMP and ERK-Dependent Pathways - Zhu, Yue; Liu, Mengqiu; Qu, Suchen; Cao, Cheng; Wei, Chongqi; Meng, Xue-er; Lou, Qianyin; Qian, Dawei; Duan, Jin-ao; Ding, Yuhua; Han, Zhengxiang; Zhao, Ming (Frontiers in Pharmacology, 2020)
Elaphuri Davidiani Cornu (EDC) is the natural shedding horn of Elaphurus davidiauus Millne-Edwards that was used by people in ancient China for maintaining physical and mental health. We evaluated the antidepressant effect of EDC using depression-like animal models and explored possible mechanisms in mouse primary astrocyte cultures. We found that aqueous extracts of EDC significantly improved depression-like behavior in a mouse model of depression. The extracts enhanced expression of nerve growth factor and brain-derived neurotrophic factor neurotrophic factors in mouse prefrontal cortex and hippocampus tissues. In the mouse primary astrocyte cultures, the EDC aqueous extracts significantly increased the neurotrophic factor expression both at the transcriptional and protein levels. EDC extracts might exhibit these functions by regulating matrix metalloprotein-9 of the nerve growth factor and brain-derived neurotrophic factor metabolic pathways and might enhance expression of neurotrophic factors via the cAMP- and ERK-dependent pathways. We confirmed this possibility by showing the effects of related inhibitors, providing scientific evidence that supports the utility of EDC in the development of drugs to treat major depressive disorders.